2008
DOI: 10.4161/cbt.7.4.5535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying selective cytotoxic activity of BZL101, an extract of Scutellaria barbata, towards breast cancer cells

Abstract: We studied the mechanism of the cytotoxic activity of BZL101, an aqueous extract from the herb Scutellaria barbata D. Don, which is currently in phase II clinical trial in patients with advanced breast cancer. The phase I trial showed favorable toxicity profile and promising efficacy. We report here that BZL101 induces cell death in breast cancer cells but not in non-transformed mammary epithelial cells. This selective cytotoxicity is based on strong induction by BZL101 of reactive oxygen species (ROS) in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 34 publications
4
62
0
Order By: Relevance
“…We further observed that treatment of MCF7 cells strongly downregulated expression of both EGFR and the ErbB2/HER2 member of the EGF receptor gene family. BZL101 was previously demonstrated to be effective in inhibiting proliferation of the HER2 + hormone insensitive SKBR3 breast cancer cell line, 17 and is well tolerated in metastatic breast of cells within the G 1 , S and G 2 /M phases of the cell cycle were determined by analyzing the histographic output with the multicycle computer program MPLUS, provided by Phoenix Flow Systems (San Diego, CA), in the Cancer Research Laboratory Microchemical Facility at the University of California at Berkeley. Western blotting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further observed that treatment of MCF7 cells strongly downregulated expression of both EGFR and the ErbB2/HER2 member of the EGF receptor gene family. BZL101 was previously demonstrated to be effective in inhibiting proliferation of the HER2 + hormone insensitive SKBR3 breast cancer cell line, 17 and is well tolerated in metastatic breast of cells within the G 1 , S and G 2 /M phases of the cell cycle were determined by analyzing the histographic output with the multicycle computer program MPLUS, provided by Phoenix Flow Systems (San Diego, CA), in the Cancer Research Laboratory Microchemical Facility at the University of California at Berkeley. Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, BZL101 is able to induce G 1 cell cycle arrest followed by apoptosis of these cancers 14,15 with effective concentrations of 2 mg/mL and 1 mg/ mL, respectively. Aqueous extracts of BZL101 contain several active anticancer compounds, 16 which are able to block glycolysis and induce cell death in a number of cancer cell lines, 17 and is well tolerated by metastatic breast cancer patients. 18 While the effect of BZL101 on the metabolic functioning of cancer cells has been studied, relatively little is known about how BZL101 regulates proliferative signaling and cell cycle control within human reproductive cancer cells.…”
Section: Bzl101 a Phytochemical Extract From Thementioning
confidence: 99%
“…Some of these isolated components of BD previously demonstrated direct cytotoxic effect on breast cancer cells. For example, extracts from medicinal mushrooms C versicolor and G lucidum, 27,28 medicinal herbs S barbata, A membranaceus, and C longa, [29][30][31] and nutritional compounds diindolylmethane and quercetin 32,33 induced apoptosis in breast cancer cells, respectively. Nevertheless, the cytotoxic activities of some isolated extracts were achieved at higher concentrations with IC 50 in the range of 72 to 514 µg/mL for MDA-MB-231 cells, 27,28 whereas BD demonstrated cytostatic effect for the same cell line at markedly lower concentrations with IC 50 22 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Significant apoptosis induction has been observed in TRAMP-C1 and LNCaP cells treated with S. barbata (1 mg/ml) (34). An aqueous extract from S. barbata, BZL101, induced the production of reactive oxygen species in tumor cells, and therefore caused extensive oxidative DNA damage leading to necrotic death (35).…”
Section: Discussionmentioning
confidence: 99%